The transcriptional regulation of VEGF production from pulmonary artery smooth muscle cells by TGFβ1 - Clifford, Rachel (2009)
Pulmonary Hypertension (PH) is a rare and fatal disease of the pulmonary vasculature. Hyperplasia and hypertrophy of smooth muscle cells in muscular arteries and arrival of smooth muscle cell in non-muscular pulmonary arteries are key pathological features of PH. VEGF has a strong role in embryonic vasculo/angiogenesis and adult vascular protection. VEGF and its main signalling receptor, VEGFR2, are expressed on endothelial and smooth muscle cells within remodelling arteries and VEGFR inhibition leads to the development of PH in rats. Furthermore over expression of VEGF in monocrotaline models of PH prevents the progression of remodelling. Here we tested the effect of mediators relevant to PH on VEGF release from pulmonary artery smooth muscle cells (PASMCs). TGFβ1 exerted the greatest effect and we went on to characterise the signal transduction and transcriptional mechanisms involved. TGFβ1 acted via two T cell factor (TCF) binding sites within the VEGF promoter and increased basal levels of TCF4 association with the VEGF promoter. TGFβ1 also induced Smad2, 3 and 4 association with the VEGF promoter within the same region as TCF4 and inhibition of Smads abolished the TGFβ1 effect. We found that a GSK3β/β-catenin/Smad2/3 nuclear complex was present under unstimulated conditions and that TGFβ1 caused inhibition of glycogen synthase kinase 3β (GSK3β) and decreased β-catenin phosphorylation. Unphosphorylated β-catenin associated with the VEGF promoter in response to TGFβ1, while phosphorylated β-catenin did not. Collectively these studies suggest that dephosphorylation of β-catenin, in response to TGFβ1, allowed association of a preformed protein complex with TCF4 at the VEGF promoter, which in turn increased VEGF transcription. Finally we showed that murine PASMCs heterozygous for BMPR II, the most commonly mutated gene in PH, produced increased VEGF protein and mRNA in response to TGFβ1 than their wild type controls.